Myocarditis with tremelimumab plus durvalumab combination therapy for endometrial cancer: A case report - Syed S. Mahmood; Carol L. Chen; Natalie Shapnik; Udhay Krishnan; Harsimran S. Singh; Vicky Makker (Gynecologic Oncology Reports, 2018)
Background: Fulminant myocarditis has been reported in patients treated with immune checkpoint inhibitors. We present the first described case of acute immune-mediated myocarditis and myositis associated with durvalumab plus tremelimumab combination therapy. The patient was undergoing treatment for advanced endometrial cancer. Case presentation: A 75-year-old Caucasian female presented with difficulty ambulating due to neck protraction, imbalance, and increased shortness of breath with exertion 3 weeks after her first durvalumab and tremelimumab administration for advanced endometrial cancer. While the patient's initial laboratory data showed an acute transaminitis and elevated creatine phosphokinase (CPK), consistent with myositis, she developed complete heart block and ventricular dysfunction, with elevated troponins. Endomyocardial biopsy confirmed a diagnosis of immune-mediated myocarditis. She was treated with high-dose steroids and mycophenolate mofetil, which led to eventual native conduction and left ventricular ejection fraction recovery. Upon discharge, she was titrated off of steroids over 8 weeks and her mycophenolate was subsequently stopped. A follow-up computed tomography scan revealed progression of metastatic disease. The patient remains alive using supplemental oxygen 3 months after admission. Conclusions: Durvalumab plus tremelimumab combination therapy can lead to fulminant immune-mediated myocarditis. This patient's myocarditis was amenable to treatment with high-dose intravenous steroids and mycophenolate. Keywords: Endometrial cancer, Durvalumab, Tremelimumab, Immune-mediated myocarditis, Cardio-oncology, Myositis